Fixed Income Markets and their Derivatives. - Jordan, Bradford D.; Sundaresan, Suresh (Journal of Finance, 1997)
The 3e of this well-respected textbook continues the tradition of providing clear and concise explanations for fixed income securities, pricing, and markets. The book matches well with fixed income securities courses. The book's organization emphasizes institutions in the first part, analytics in the second, selected segments of fixed income markets in the third, and fixed income derivatives in the fourth. This enables instructors to customize the material to suit their course structure and the mathematical ability of their students. In this title, new material on Credit Default Swaps, Collateralized Debt Obligations, and an integrated discussion of the Credit Crisis have been added. Online Resources for instructors on password protected website provides worked out examples for each chapter. A detailed description of all key financial terms is provided in a glossary at the back of the book.